One-step synthesized antimicrobial peptide-functionalized gold nanoclusters for selective imaging and killing of pathogenic bacteria - Shen, Yunqiu; Zheng, Chaochuan; Wu, Qiaoli; Wu, Qilong; Jin, Ming; Jiang, Yayun; Huang, Fuyuan; Lou, Yongliang; Zheng, Laibao (Frontiers in Microbiology, 2022)
The development of multifunctional nanomaterials with bacterial imaging and killing activities is of great importance for the rapid diagnosis and timely treatment of bacterial infections. Herein, peptide-functionalized gold nanoclusters (CWR11-AuNCs) with high-intensity red fluorescence were successfully synthesized via a one-step method using CWR11 as a template and by optimizing the ratio of CWR11 to HAuCl4, reaction time, pH, and temperature. The CWR11-AuNCs bound to bacteria and exhibited selective fluorescence microscopy imaging properties, which is expected to provide a feasible method for locating and imaging bacteria in complex in vivo environments. In addition, CWR11-AuNCs not only retained the antibacterial and bactericidal activities of CWR11 but also exhibited certain inhibitory or killing effects on gram-negative and gram-positive bacteria and biofilms. The MICs of CWR11-AuNCs against Escherichia coli and Staphylococcus aureus were 178 and 89 μg/ml, respectively. Surprisingly, cell viability in the CWR11-AuNC-treated group was greater than that in the CWR11-treated group, and the low cytotoxicity exhibited by the CWR11-AuNCs make them more promising for clinical applications.